2016
DOI: 10.4081/ijfs.2016.5706
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the presence of domoic acid in the production areas of bivalve molluscs

Abstract: Algal biotoxins, chemical compounds produced by some microscopic algae, constitute the phytoplankton. The mussels, feeding on phytoplankton, can accumulate these compounds to become themselves toxic. There have been several cases of food poisoning by consumption of contaminated shellfish. Such food poisoning have pushed our health care system to provide monitoring of shellfish in the framework of the monitoring plans carried out by AASSLL. In this paper we report the results obtained monitoring the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…S1), with abundances up to several million cells•L -1 (e.g., Caroppo et al, 2005;Cerino et al, 2005;Quiroga et al, 2006;Quijano-Scheggia et al, 2008;Ljubešić et al, 2011;Marić et al, 2011;Cabrini et al, 2012;Ruggiero et al, 2015;Taş and Lundholm, 2017;Totti et al, 2019a). Nevertheless, the detection of DA has caused the closure of aquaculture plants only in a limited number of cases (4% of toxicity events in HAEDAT) in southern Spain (HAEDAT) and France (Amzil et al, 2001), whereas DA values below the regulatory limit have occasionally been found in shellfish from the Adriatic Sea (Ciminiello et al, 2005;Ujević et al, 2010;Arapov et al, 2016), Greece (Kaniou-Grigoriadou et al, 2005), and in 65% of 180 mussel samples from mid-Tyrrhenian waters (Rossi et al, 2016). In a few cases, the presence of DA in bivalves was related to a specific taxon, i.e., P. calliantha along the Croatian coast (Marić et al, 2011) and in the Gulf of Trieste (Honsell et al, 2008) and P. brasiliana in the Bizerte Lagoon in Tunisia (Sahraoui et al, 2011).…”
Section: Amnesic Shellfish Poisoning (Asp)mentioning
confidence: 99%
“…S1), with abundances up to several million cells•L -1 (e.g., Caroppo et al, 2005;Cerino et al, 2005;Quiroga et al, 2006;Quijano-Scheggia et al, 2008;Ljubešić et al, 2011;Marić et al, 2011;Cabrini et al, 2012;Ruggiero et al, 2015;Taş and Lundholm, 2017;Totti et al, 2019a). Nevertheless, the detection of DA has caused the closure of aquaculture plants only in a limited number of cases (4% of toxicity events in HAEDAT) in southern Spain (HAEDAT) and France (Amzil et al, 2001), whereas DA values below the regulatory limit have occasionally been found in shellfish from the Adriatic Sea (Ciminiello et al, 2005;Ujević et al, 2010;Arapov et al, 2016), Greece (Kaniou-Grigoriadou et al, 2005), and in 65% of 180 mussel samples from mid-Tyrrhenian waters (Rossi et al, 2016). In a few cases, the presence of DA in bivalves was related to a specific taxon, i.e., P. calliantha along the Croatian coast (Marić et al, 2011) and in the Gulf of Trieste (Honsell et al, 2008) and P. brasiliana in the Bizerte Lagoon in Tunisia (Sahraoui et al, 2011).…”
Section: Amnesic Shellfish Poisoning (Asp)mentioning
confidence: 99%
“…Marine toxins can be categorized as lipophilic or hydrophilic, based on their solubility [ 3 ]. Hydrophilic toxins are distributed globally [ 4 , 5 , 6 , 7 , 8 ], especially saxitoxin (STX) and domoic acid toxin groups, which cause paralytic and amnesic shellfish poisoning, respectively [ 9 , 10 , 11 , 12 ]. However, more than 90% of marine toxins are lipophilic [ 13 ], with examples including okadaic acid (OA) and its analogs dinophysistoxins (DTXs), pectenotoxins (PTXs), azaspiracids, yessotoxins (YTXs), spirolids, gymnodimines, and pinnatoxins, collectively known as lipophilic shellfish toxins (LSTs) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%